Forecasting Occurrence and Intensity of Geomagnetic Activity With Pattern‐Matching Approaches - C. Haines; M. J. Owens; L. Barnard; M. Lockwood; A. Ruffenach; K. Boykin; R. McGranaghan (Space Weather)
Abstract Variability in near‐Earth solar wind conditions gives rise to space weather, which can have adverse effects on space‐ and ground‐based technologies. Enhanced and sustained solar wind coupling with the Earth's magnetosphere can lead to a geomagnetic storm. The resulting effects can interfere with power transmission grids, potentially affecting today's technology‐centered society to great cost. It is therefore important to forecast the intensity and duration of geomagnetic storms to improve decision making capabilities of infrastructure operators. The 150 years aaH geomagnetic index gives a substantial history of observations from which empirical predictive schemes can be built. Here we investigate the forecasting of geomagnetic activity with two pattern‐matching forecast techniques, using the long aaH record. The techniques we investigate are an Analogue Ensemble (AnEn) Forecast, and a Support Vector Machine (SVM). AnEn produces a probabilistic forecast by explicitly identifying analogs for recent conditions in the historical data. The SVM produces a deterministic forecast through dependencies identified by an interpretable machine learning approach. As a third comparative forecast, we use the 27 days recurrence model, based on the synodic solar rotation period. The methods are analyzed using several forecast metrics and compared. All forecasts outperform climatology on the considered metrics and AnEn and SVM outperform 27 days recurrence. A Cost/Loss analysis reveals the potential economic value is maximized using the AnEn, but the SVM is shown as superior by the true skill score. It is likely that the best method for a user will depend on their need for probabilistic information and tolerance of false alarms.